Can changes of workrate and seat position affect frontal and sagittal plane knee biomechanics in recumbent cycling? - Lu, T.; Thorsen, T.; Porter, J. M.; Weinhandl, J. T.; Zhang, S. (Sports Biomechanics, 2023)
Changes in the workrate and seat position have been linked to changes in internal knee extension moment. However, there is limited research on effects of those changes on knee kinetics in recumbent bike. The purpose of this study was to examine the effects of different seat positions and workrates on KAbM, knee extension moment and perceived effort during stationary recumbent cycling. Fifteen cyclists cycled on a recumbent ergometer in 6 test conditions of pedalling in far, medium and close seat positions in each of the two workrates of 60 and 100 W at the cadence of 80 RPM. A three-dimensional motion analysis system and a pair of instrumented pedals collected kinematic and kinetic data. A 3 ×2 repeated measures ANOVA was used to examine the effect of seat positions and workrates on selected variables of interest. Different seat positions did not change either peak KAbM (p = 0.592) or knee extension moment (p = 0.132). Increased workrates significantly increased peak KAbM (p <0.001 and np2 =0.794) and knee extension moment (p <0.001 and np2=0.722). This study showed that the far or close seat position did not increase frontal-plane or overall knee joint loading and provided evidence for prescribing recumbent bike for healthy population.